Efektivitas Meningkatkan Pengetahuan & Kesadaran Masyarakat Membayar Pajak Penghasilan di Desa Simpang Pelabuhan Dalam - Pitaloka, Indah; Gustini , Emilia (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
Community service in villages through the Thematic Real Work Lecture (KKNT) program. Student participation in solving community problems. This research aims to find out the contribution of KCN students in educating the public about paying income tax and increasing tax awareness in the Ogan Iliri Regency Community, Pemulutan District, Simpang Pelabuhan Dalam. This research uses a method, namely direct contact with the people who live at Simpang Belabuhan Dal. Core KKN students took part in an outreach campaign to the community about the importance of tax education and paying income tax, as well as tax education and opening an account with a NPWP for village communities at Simpang Pilabhuhan Dalam. The results of this research show tax efficiency and increase tax knowledge and income tax culture. For further information, please contact the KKN manager in Simpang Pelabuhan Dalam Village. The community is starting to understand the importance of paying school fees regarding taxation, showing an increase in effectiveness and efficiency by Thematic KKN students.